Process warehouse based agent's competencies measurement method for business process improvement - Sohail, A. (Institute of Electrical and Electronics Engineers Inc., 2016)
Enterprises are continuously aiming at improving execution of processes in order to achieve competitive edge. One of established ways of improving process performance is to assign most appropriate resources to each task of the process. However, an evaluation of business process improvement approaches have established that a method that can guide the task of process improvement in a structured way is missing. To address this problem the aim of this research is to present a method that can compute competency of resources. The computed competencies serve as a basis for choosing most appropriate resource for each task of the process. The applicability of the proposed method is illustrated with health care example. Â© 2016 IEEE.